2013
DOI: 10.1002/jmri.23998
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dixon and T1‐weighted MR methods to assess the degree of fat infiltration in duchenne muscular dystrophy patients

Abstract: There are minor differences between the various lipid spectral models in terms of quantifying fat fraction in a large number of skeletal muscles in the legs of Duchenne patients and healthy controls. Quantitative 3-point Dixon MRI is more precise and reliable than visual radiological methods for evaluation of fat fractions for potential longitudinal follow-up or therapy evaluation of Duchenne patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(133 citation statements)
references
References 25 publications
6
121
0
6
Order By: Relevance
“…This is consistent with previous cross-sectional studies in FSHD [27][28][29] and in other MRI studies in muscular dystrophies [14,15]. This relationship was not found for the longitudinal measurements.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous cross-sectional studies in FSHD [27][28][29] and in other MRI studies in muscular dystrophies [14,15]. This relationship was not found for the longitudinal measurements.…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies, qMRI has been used to describe the natural progression of neuromuscular disorders such as oculopharyngeal muscular dystrophy, Charcot-Marie-Tooth disease 1A, inclusion body myositis, LGMD2I and dystrophinopathies [13][14][15][16][17][18][19] and to characterize changes resulting from therapeutic trials [20]. Overall, it has been shown that muscle MRI can be more sensitive than clinical scores to detect disease progression during the follow-up of patients with muscular dystrophies [14,15] thereby highlighting the qMRI potential for the noninvasive assessment of disease progression and the characterization of treatment efficiency in neuromuscular disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Ignorer les autres résonances lipidiques génère un certain degré d'imprécision (Wokke et al 2013). Celle-ci peut être réduite par une modélisation plus complète du spectre des lipides, habituellement avec 3 ou 4 résonances principales, ce qui nécessite la collecte de 6 échos et des calculs relativement lourds (Hu et al 2012).…”
Section: Les Altérations Dégénératives Chroniquesunclassified
“…En combinant les pourcentages de graisse avec une segmentation manuelle des muscles, on a pu déterminer des indices de masse contractile chez les patients atteints de la maladie de Duchenne (Wokke et al 2014b). La confrontation des cartographies de pourcentages de graisses au classement de Lamminen a montré une surestimation systématique des changements dégé-nératifs avec les méthodes qualitatives (Wokke et al 2013). Toujours dans la maladie de Duchenne, l'exploration des avant-bras en imagerie a montré une implication plus importante des muscles fléchisseurs que des extenseurs, et une progression plus rapide des lésions dégénératives graisseuses chez les patients ayant perdu l'ambulation que chez les patients ambulants (Wary et al 2015b ;Hogrel et al 2016).…”
Section: Les Altérations Dégénératives Chroniquesunclassified
“…Игнорирование других липидных ответов приводит к некоторым неточностям [63]. Этот процесс можно усовершенствовать за счет лучшего моделирования липидного спектра.…”
Section: лекции и обзорыunclassified